Immunohistochemical analysis of HLA (A, B, C) antigens in liver disease using a monoclonal antibody. Issue 12 (December 1981) - Barbatis, C; Woods, J; Morton, J A; Fleming, K A; McMichael, A; McGee, J O
Abstract : The distribution of HLA class I antigens was studied in 42 liver biopsies and eight necropsies by an immunoperoxidase technique employing a monoclonal antibody which reacts with the heavy chains of class I (A, B, C) HLA antigens. In normal liver HLA class I antigens could not be detected on hepatocyte cell membranes or cytoplasm; these antigens were present on the cell membrane of bile duct epithelium, on sinusoidal lining cells, fibroblasts, and blood vessel endothelium. However, in all patients with acute alcoholic hepatitis, most cases of primary biliary cirrhosis and some cases of chronic active hepatitis HLA class I antigens were detectable focally or diffusely on the cell membrane of hepatocytes; in two cases of acute viral hepatitis (non-A, non-B) HLA class I antigens were present in granular form in the cytoplasm of all hepatocytes. These findings may be relevant to the prolonged survival of liver allografts in man and other species and in the pathogenesis of some liver diseases.